Integrated E-Learning Design in Mathematical Sciences - H Purnomo; R E P Lubis; F R Somantri; J R Herijon; D Oktafiani (Peneliti.net, 2021)
Mathematics is the foundation of science in the industrial era 4.0. The need for technology has become an industry-standard in today’s modern era and the need for quality human resources in the IT field. The purpose of this study is to analyze the integrated e-learning design in mathematics. The research method used is a descriptive method by collecting data and describing students' problems around mathematics. The object of this research is the students of Universitas Komputer Indonesia. The results showed that E-Learning is one of the media in improving and improving the quality of student learning applied in mathematics because mathematics is the basis of science and technology for modern science. It is because the integrated e-learning design makes it easier for students to find formula knowledge. In conclusion, the use of e-learning is one way to improve the understanding of mathematics among students. Besides, it can be a reference for all formulas and branches of mathematics believed to help students find the mathematical